Partisipasi Publik yang Bermakna dalam Pembentukan Undang-Undang Pasca Kontroversi Legislasi 2025 (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines meaningful public participation in the making of legislation after the legislative controversies of 2025 in Indonesia. The issue is constitutionally significant because the legitimacy of legislation in a democratic rule-of-law state depends not only on formal enactment, but also on whether the public is genuinely involved in the legislative process. Using normative legal research with statutory, conceptual, and case approaches, this article analyses the 1945 Constitution, Law Number 12 of 2011, Law Number 13 of 2022, and Constitutional Court Decision Number 82/PUU-XXI/2023, supported by academic legal writings on public participation. The article argues that Indonesian legislation already recognizes participation rights, but the implementation remains vulnerable to procedural formalism, delayed access to bill documents, and weak feedback mechanisms. After the 2025 legislative controversies, the strengthening of meaningful participation requires open access to draft laws, timely involvement of affected groups, documented legislative responses, and technical rules that prevent public participation from being reduced to symbolic consultation.
Keywords: Public Participation; Law-Making; Constitutional Process; Meaningful Participation; Legislative Governance